Perancangan Alat Penyemprot Hama Pertanian Otomatis Bertenaga Surya dengan Menggunakan Metode Quality Function Deployment (Studi Kasus: Petani Bangkalan Madura) - Saputro, Andre Ridho; Putra, Andhika Cahyono; Kusnanto, Hadi; Alfi, Aisyah (Universitas Muhammadiyah Tangerang, 2024)
In the modern era, the application of technology in agriculture (agrotechnology) has become an innovative solution to overcome various agricultural problems, including pest control. Lack of effectiveness in pest control is often a complex problem faced by farmers in Indonesia. One innovation that has attracted attention is the development of automatic pest spraying equipment. This tool is designed to optimize the pest spraying process by utilizing advanced technology such as remote sensors and renewable energy. This research aims to design a pest spraying tool using the Quality Function Deployment (QFD) method to accommodate farmers' needs and the technical responses that will appear in the designed tool. The results of this research are a design for an automatic pest sprayer equipped with a remote sensor that offers several advantages. First, this tool is able to detect the presence of pests or the need for spraying from a distance, allowing for more targeted spraying. Second, the use of solar power as the main energy source makes this tool environmentally friendly and capable of operating independently without requiring an external power source. Third, automation in pest spraying can reduce the need for manual labor and increase the efficiency of pesticide use